The barriers and facilitators that indigenous health workers experience in their workplace and communities in providing self-management support: a multiple case study - Jessica Conway; George Tsourtos; Sharon Lawn (BMC Health Services Research, 2017)
Abstract Background The inequality in health outcomes between Indigenous (Throughout the paper, the term Indigenous will be used to represent both Aboriginal Australians and Torres Strait Islander Australians.) and non-Indigenous Australians continues to be a major public health issue. Chronic conditions are responsible for the majority of the gap in life expectancy for this population. Evidence suggests that chronic condition management models focusing on self-management have led to improved health outcomes in Indigenous populations. The Flinders Closing the Gap Program (FCTGP) is a chronic condition care planning tool which aims to engage Indigenous people in self-managing their chronic conditions. Indigenous health workers (IHWs) can provide culturally appropriate self-management support; however there is paucity in current literature describing specific barriers and facilitators that they may experience when attempting to deliver this support. This study aimed to explore IHWs’ perceptions of the effectiveness and appropriateness of the FCTGP, as an evidence-based example of self-management support, and to explore the barriers and facilitators that IHWs experience in their workplace and communities in providing self-management support. Methods In-depth interviews were undertaken with five IHWs, drawn from five different states in Australia. Their selection was aided by key informants from the FCTGP training unit. Interviews were recorded and transcribed verbatim, and were analysed using thematic analysis. Results The following themes were identified. IHWs reported that the FCTGP was appropriate, flexible and acceptable in their communities. Facilitators included factors improving client and worker empowerment, and activities around sharing knowledge. Barriers included competing priorities that clients experience relating to social determinants of health, and negative experiences within mainstream health services. IHW burnout from time pressures, lack of support, and high staff turnover were also considered important barriers. Conclusions This study contributes an insight into the experiences of IHWs who are considered important stakeholders in implementation and sustainability of chronic condition management programs, including the FCTGP. Recommendations focus on supporting and supplementing the role of IHWs and identify the FCTGP as a facilitator in providing self-management support to a population with complex needs.